Versatile UPQC Control System with a Modified Repetitive Controller under Nonlinear and Unbalanced Loads - Trinh, Quoc-Nam (2015)
A standard repetitive controller (RC) is theoretically able to replace a bank of resonant controllers in harmonic signals tracking applications. However, the traditional RC has some drawbacks such as a poor dynamic response and a complex structure to compensate grid frequency deviations for an effective unified power quality conditioner (UPQC) control scheme. In order to solve these problems, an improved RC with an outstanding dynamic response and a simplified grid frequency adaptive scheme is proposed for UPQC control systems in this paper. The control strategy developed for the UPQC has delay time, i.e., one-sixth of a fundamental period (Tp/6), repetitive controllers. As a result, the UPQC system can provide a fast dynamic response along with good compensation performance under both nonlinear and unbalanced loads. Furthermore, to guarantee the excellent performance of the UPQC under grid frequency deviations, a grid frequency adaptive scheme was developed for the RC using a simple first order Padé's approximation. When compared with other approaches, the proposed control method is simpler in structure and requires little computing time. Moreover, the entire control strategy can be easily implemented with a low-cost DSP. The effectiveness of the proposed control method is verified through various experimental tests.